Effect of Manganese Content and Cooling Rate on the Formation of AlFeMn Intermetallic Phases in 8006 Aluminum Alloy - Ozcetin, Yusuf; Denizli, Feyza; Ulus, Ali; Balkan, Harun; Sazci, Oguler; Gecu, Ridvan (SPRINGER INTERNATIONAL PUBLISHING AG, 2026)
This study investigates the effect of manganese (Mn) content on the formation of coarse AlFeMn intermetallic phases in 8006 aluminum alloy, which is used for foil production, under varying cooling rates. Alloys with 0.35, 0.65, and 0.85% Mn content were cast, while other alloying elements were kept constant. The castings were subjected to different cooling rates using the TP1 test setup, and the impact of slow self-cooling was also examined. The microstructural characterization was performed using optical microscopy and SEM imaging. Results reveal the influence of Mn concentration and cooling rate on the formation of AlFeMn intermetallic phases, providing valuable insights for optimizing alloy composition and improving the casting quality of 8006 aluminum foil in industrial applications.
Keywords: Aluminium; Solidification; Intermetallics; Characterization; Science & Technology - Other Topics; Engineering; Materials Science; Metallurgy & Metallurgical Engineering